Postindustrial East Asian Cities : Innovation for Growth - Yusuf, Shahid; Nabeshima, Kaoru (Washington, DC : World Bank and Stanford University Press, 2012)
Post-Industrial East Asian Cities analyzes urban developments and policies responsible for the growth of producer services and creative industries. This study is based on the findings of firm surveys conducted in East Asia and a review of the data and literature on several key regional cities (Beijing, Shanghai, Singapore, Seoul, Bangkok and Tokyo) that are transitioning away from traditional manufacturing activities.